2024
DOI: 10.3390/antiox13020209
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perilipins in Oxidative Stress—Implications for Cardiovascular Disease

Mathieu Cinato,
Linda Andersson,
Azra Miljanovic
et al.

Abstract: Oxidative stress is the imbalance between the production of reactive oxygen species (ROS) and antioxidants in a cell. In the heart, oxidative stress may deteriorate calcium handling, cause arrhythmia, and enhance maladaptive cardiac remodeling by the induction of hypertrophic and apoptotic signaling pathways. Consequently, dysregulated ROS production and oxidative stress have been implicated in numerous cardiac diseases, including heart failure, cardiac ischemia–reperfusion injury, cardiac hypertrophy, and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 133 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…Then, these synthesized LTAG could bind apolipoprotein B100 (APOB100) and enter the bloodstream by free diffusion [102]. Meanwhile, Plin2, as a key lipid droplet coated protein, is tightly related with lipid droplet biogenesis and storage in tissues [103]. Elevated levels of Plin2 are often associated with various metabolic disorders, including insulin resistance and type 2 diabetes in human and animals [103,104].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, these synthesized LTAG could bind apolipoprotein B100 (APOB100) and enter the bloodstream by free diffusion [102]. Meanwhile, Plin2, as a key lipid droplet coated protein, is tightly related with lipid droplet biogenesis and storage in tissues [103]. Elevated levels of Plin2 are often associated with various metabolic disorders, including insulin resistance and type 2 diabetes in human and animals [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Plin2, as a key lipid droplet coated protein, is tightly related with lipid droplet biogenesis and storage in tissues [103]. Elevated levels of Plin2 are often associated with various metabolic disorders, including insulin resistance and type 2 diabetes in human and animals [103,104]. The study found that FABP10, GPAT3, GPAT4, DGAT2, APOB100, and Plin2 levels were notably higher in groups consuming high-starch diets, consistent with earlier findings in largemouth bass [18] and gilthead sea bream [105].…”
Section: Discussionmentioning
confidence: 99%
“…Langer et al reported that PDA is almost completely degraded at 8 weeks after entry into organisms (Bettinger et al, 2009). PDA nanoparticles lose UV absorption in the presence of hydrogen peroxide (H 2 O 2 ) and are accompanied by color fading, whereas reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is widely present in phagocytes and in many organs and is capable of generating H 2 O 2 , an endogenous molecule, which suggests that PDA can be biodegraded in vivo (Liu et al, 2013;Cinato et al, 2024).…”
Section: Biodegradabilitymentioning
confidence: 99%